Pelatihan Penerapan Teknologi Mesin Retort Cerdas untuk Menambah Daya Simpan Produk Olahan Jamur Tiram bagi Anggota Kelompok UPPKA Rizky Lancar Kelurahan Pongangan Gunungpati Semarang: Training on the Application of Smart Retort Machine Technology to Increase the Shelf Life of Processed Oyster Mushroom Products for UPPKA Group Members Rizky Lancar, Pongangan Village, Gunungpati, Semarang - Sukur, Muji; Februariyanti, Herny; Sari, Anisa Rachma; Nurraharjo, Eddy (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Food preservation is a crucial aspect of the food industry, especially to extend shelf life, maintain quality, and ensure consumption safety. Preservation methods such as pasteurization and sterilization effectively inhibit the growth of pathogenic microorganisms without reducing the nutritional value of food. The UPPKA "Rizky Lancar" group in Pongangan Village, Semarang, has developed a business cultivating and processing oyster mushrooms into various products such as satay, meatballs, and nuggets. However, they face several challenges, including short product shelf life, unstable raw material supply, limited processing and packaging technology, and limited marketing reach. To overcome these problems, the Community Partnership Program team provides training and assistance that includes the application of appropriate technology such as a microcontroller-based food sterilization machine to optimally control temperature and pressure. Students are also involved through a student-centered learning model, with contributions in literacy studies, system development, implementation of information technology for marketing, and protection of intellectual property rights and scientific publications. Product diversification efforts are also carried out by developing various innovations in oyster mushroom processing that can be preserved, thus expanding product variations and meeting various consumer preferences. These new products are expected to increase competitiveness in the market and open up wider marketing opportunities. The expected results of this program include increasing the shelf life and quality of processed mushroom products, expanding the range of products through diversification of preserved products, increasing production capacity and efficiency through the use of modern technology, and strengthening marketing strategies based on information technology.